Indian elections 2014: The 'alternative' and 'critical' online. Issue 1 (May 2016) - Ranganathan, Maya
The Indian national election in 2014 marked the emergence of social media as a significant site of political campaigning. The sweeping of the polls by the Bharatiya Janata Party (BJP), led by the party's prime ministerial candidate, Gujarat chief minister Narendra Modi, who employed social media extensively in his campaign, has drawn further attention to the hitherto 'alternative media' space. 'Alternative media' has been positioned and studied in relation to mainstream media. This article illustrates the ways in which the perceptions of mainstream media in a liberalised economy contoured the 'alternative media' space, limiting its potential to lead to radical and transformative processes of communication. In the process, the article interrogates the online space occupied by political parties and activists in the context of theoretical understandings of 'alternative' and 'critical' media. The article flags the need for, and the significance of, sustained study of the emerging new media space to understand the process of reconstitution of the Indian public space.